26 T 35 mm all-GdBa2Cu3O7–x multi-width no-insulation superconducting magnet. (10th March 2016) - Yoon, Sangwon; Kim, Jaemin; Cheon, Kyekun; Lee, Hunju; Hahn, Seungyong; Moon, Seung-Hyun
Abstract: A 26 T 35 mm winding diameter all-GdBa2 Cu3 O 7 − x (GdBCO) magnet was designed by the MIT Francis Bitter Magnet Laboratory, and constructed and tested by the SuNAM Co., Ltd. With the multi-width (MW) no-insulation (NI) high temperature superconductor (HTS) winding technique incorporated, the magnet is highly compact; its overall diameter and height are 172 and 327 mm, respectively. It consists of a stack of 26 NI double pancake coils wound with MW GdBCO tapes in five different widths ranged 4.1–8.1 mm. In a bath of liquid nitrogen at 77 K, the magnet had a charging time constant of 16 min due to the intrinsic NI characteristics. In liquid helium at 4.2 K, the magnet generated a 26.4 T field at the center, a record high in magnetic fields from all-HTS magnets. The results demonstrate a strong potential of MW-NI GdBCO magnets for direct current high-field applications.